2006 Sixth IEEE International Workshop on Source Code Analysis and Manipulation 2006
DOI: 10.1109/scam.2006.20
|View full text |Cite
|
Sign up to set email alerts
|

Normalizing Metamorphic Malware Using Term Rewriting

Abstract: Metamorphic malware -including certain viruses and worms -rewrite their code during propagation. This paper presents a method for normalizing multiple variants of metamorphic programs that perform their transformations using finite sets of instruction-sequence substitutions. The paper shows that the problem of constructing a normalizer can, in specific contexts, be formalized as a term rewriting problem. A general method is proposed for constructing normalizers. It involves modeling the metamorphic program's t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…Traditional static analysis approaches such as [38], [46], which focus on comparing programs with known malware based on the program code, looking for signatures using other heuristics. Other approaches [47], [48], [49] focus on using machine learning and data mining approaches for malware detection. In [49], Tesauro et al train a neural network to detect boot sector viruses, based on bytestring trigrams.…”
Section: Detection Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional static analysis approaches such as [38], [46], which focus on comparing programs with known malware based on the program code, looking for signatures using other heuristics. Other approaches [47], [48], [49] focus on using machine learning and data mining approaches for malware detection. In [49], Tesauro et al train a neural network to detect boot sector viruses, based on bytestring trigrams.…”
Section: Detection Approachesmentioning
confidence: 99%
“…Other approaches [47], [48], [49] focus on using machine learning and data mining approaches for malware detection. In [49], Tesauro et al train a neural network to detect boot sector viruses, based on bytestring trigrams. Schultz et al [48] compare three machine learning algorithms trained on three features: DLL and system calls made by the program, strings found in the program binary, and a raw hexadecimal representation of the binary.…”
Section: Detection Approachesmentioning
confidence: 99%
“…More recently, metamorphic malware has appeared, which randomly applies binary transformations to its code segment during propagation in order to obfuscate features in the unencrypted portion. An example is the MetaPHOR system (c.f., [10]), which has become the basis for many other metamorphic malware propagation systems. Reversing these obfuscations to obtain reliable feature sets for signature-based detection is the subject of much current research [9,11,12], but case studies have shown that current antivirus detection schemes remain vulnerable to simple obfuscation attacks until the detector's signature database is updated to respond to the threat [13].…”
Section: Related Workmentioning
confidence: 99%
“…1 To defeat such a detector, we could have resorted to a more powerful metamorphic obfuscator such as the MetaPHOR system (c.f., [10]). MetaPHOR disassembles x86 binary code to a simplified intermediate language in which common sequences of instructions are expressed as single operations.…”
Section: Feature Removalmentioning
confidence: 99%
See 1 more Smart Citation